Electrochromism of Electropolymerized Metallophthalocyanines - KOCA, ATIF (ELECTROCHEMICAL SOC INC, 2014)
In this paper, metallophthalocyanines (MPcs; M = 2H(+) (H2Pc); Ni2+ (NiPc) and Cu2+ (CuPc)) bearing electropolymerizable amino substituents were easily and controllably electropolymerized on the working electrodes as thin solid films and electrochromic properties of these films were studied in detail with the various electrochemical, in-situ spectroelectrochemical and in-situ electrocolorimetric analysis methods. Although H2Pc and CuPc showed reasonable electrochromic features, NiPc illustrated excellent electrochromic responses with the fast response times, high optic contrast and better optical and coulombic stabilities. Although, monomeric H2Pc, NiPc, and CuPc did not behave as electrochromic materials, surprisingly the electropolymerized films of these complexes illustrated electrochemically triggered color changes between cyan and yellow or red colors. H2Pc is the first example of the metal free phthalocyanine, whose electropolymerized film behaved as an anodic coloring material. (C) 2013 The Electrochemical Society. All rights reserved.
Keywords: LUTETIUM(III) PHTHALOCYANINE; FILMS; GREEN; AL